Evaluation of single nucleotide polymorphisms in the phosphodiesterase 4D gene (PDE4D) and their association with ischaemic stroke in a large German cohort. Issue 4 (16th March 2006) - Kuhlenbäumer, G; Berger, K; Huge, A; Lange, E; Kessler, C; John, U; Funke, H; Nabavi, D G; Stögbauer, F; Ringelstein, E B; Stoll, M
Abstract : Genetic fine mapping of the first locus identified for genetically complex forms of stroke, STRK1 (which has been mapped to chromosome 5q12 in Icelandic families), has identified the phosphodiesterase 4D gene ( PDE4D ) gene as a good candidate gene. Association analysis of single nucleotide polymorphisms (SNPs) in the PDE4D gene in an Icelandic stroke cohort demonstrated genetic association between six SNPs in the 5′ region of PDE4D and ischaemic stroke. The present study aimed to test whether the same six SNPs in PDE4D were also associated with stroke in a large stroke cohort from northern Germany (stroke patients with acute completed ischaemic stroke: n = 1181; population based controls: n = 1569). None of the six SNPs showed significant association with ischaemic stroke in the whole stroke sample before and after adjustment for conventional stroke risk factors (age, sex, hypertension, diabetes, and hypercholesterolaemia). Haplotype analysis did also not reveal any significant association. Marginally positive statistical measures of association in the subgroup with cardioembolic stroke did not remain significant after correction for multiple testing. In conclusion, this study was unable to demonstrate an association between the six SNPs which had showed significant single marker association with stroke in the Icelandic stroke cohort and ischaemic stroke in a large German cohort.